Ketimpangan Gender dalam Pembangunan Ekonomi Lokal: Studi Empiris Kemiskinan Perempuan pada Masyarakat Batak Angkola di Kota Padangsidimpuan - Juwita Handayani; Lilis Saryani; Edison Siregar; Muhammar Syafii (Indo Publishing, 2026)
Gender inequality remains a structural problem in local economic development that directly contributes to the persistence of women’s poverty, particularly within societies characterized by patriarchal socio-cultural systems. This study aims to analyze the impact of gender inequality on women’s poverty among the Batak Angkola community in Padangsidimpuan City. The research employs a quantitative approach with an explanatory research design. Data were collected through a survey of working-age women from low-income households, selected using purposive sampling. Gender inequality is measured through indicators of educational attainment, women’s economic participation, access to economic resources, and patriarchal social norms, while women’s poverty is assessed based on income levels and household economic vulnerability. Data analysis was conducted using multiple linear regression to examine the relationships among variables. The findings indicate that women’s educational attainment and economic participation have a significant effect in reducing women’s poverty, whereas patriarchal norms exert a negative influence by increasing women’s economic vulnerability. These results underscore the critical role of gender inequality in shaping inclusive local economic development outcomes. This study recommends the formulation of gender-responsive local economic development policies through improved access to education, women’s economic empowerment, and the transformation of social norms as sustainable strategies for reducing women’s poverty.